Run healthy the runner's guide to injury prevention and treatment - Aguillard, Emmi 1991-
"The book offers the latest science-based guidelines for identifying, healing, and preventing the most common injuries experienced by road and trail runners. Readers will discover how the runner's body functions and responds to training, how to identify an injury, when rest is necessary, and when to seek professional treatment. Specific information on the feet and toes, ankles, knees, hips, and low back, including ways to keep these areas of the body safe and strong, is followed by coverage of specific conditions, including plantar fasciitis, Achilles tendinitis, shin splints, hamstring tendinitis and tendinopathy, and IT band syndrome"--Provided by publisher.